The Investigative Competencies from the Teaching Pedagogical Practice in Secondary Basic Education (Docentes 2.0 Journal, 2023)
Education, over time, has been a fundamental pillar in society's political, economic, and cultural transformation. Still, teachers need more investigative skills and actions in their pedagogical practices to generate innovative and transformative knowledge. The present essay was established under the humanist paradigm, in the deductive method, with a qualitative approach of an interpretive type and a narrative topic design. The purpose is to reflect on the development of the investigative competencies from the pedagogical practice in teachers of basic secondary education; this allows the realization of value judgments of the teaching role as a researcher in this type of education. In this sense, the theoretical approaches and judgments associated with the investigative competencies and the pedagogical practice for forming and developing said competencies that account for the professional performance of teachers concerning research from their pedagogical practices are presented. It is concluded that there need to be more research skills in teachers, which must be developed with a novel proposal from the reality of their pedagogical practices, leading to the production of relevant knowledge in students, which implies participation in teaching.
Keywords: Competencies; investigative competencies; pedagogical practice; initial training